2019
DOI: 10.2147/cmar.s211856
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long noncoding RNA SNHG16 silencing inhibits the aggressiveness of gastric cancer via upregulation of microRNA-628-3p and consequent decrease of NRP1</p>

Abstract: Background: MicroRNA-628-3p (miR-628) has been reported to play important roles in the progression of multiple human cancer types. Nonetheless, whether the expression profile of miR-628 is altered in gastric cancer remains unclear and whether its aberrant expression plays a crucial part in the aggressiveness of gastric cancer is yet to be determined. Therefore, in this study, we systematically investigated the involvement of miR-628 in gastric cancer progression. Materials and methods: MiR-628 expression in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
(42 reference statements)
0
16
2
Order By: Relevance
“…Luciferase reporter assay was conducted to assess the binding between ZFPM2-AS1 and miR-511-3p in cervical cancer cells. 38 FGFR2 3′ untranslated region (UTR) fragments containing either the predicted wildtype (WT) miR-511-3p-binding site or a mutant (MUT) binding site were amplified by GenePharma Technology. The amplified fragments were cloned into the pmirGLO luciferase reporter vector (Promega, Madison, WI, USA) to respectively create luciferase reporter plasmids WT-FGFR2 and MUT-FGFR2.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…Luciferase reporter assay was conducted to assess the binding between ZFPM2-AS1 and miR-511-3p in cervical cancer cells. 38 FGFR2 3′ untranslated region (UTR) fragments containing either the predicted wildtype (WT) miR-511-3p-binding site or a mutant (MUT) binding site were amplified by GenePharma Technology. The amplified fragments were cloned into the pmirGLO luciferase reporter vector (Promega, Madison, WI, USA) to respectively create luciferase reporter plasmids WT-FGFR2 and MUT-FGFR2.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…[11][12][13] Notably, lncRNAs may serve as either tumor suppressors or oncogenic molecules and participate in the regulation of malignant characteristics of GC during GC progression. [14][15][16] MicroRNAs (miRNAs) comprise another group of noncoding RNA molecules, of 17-25 nucleotides in length. 17 They can directly interact with the 3′ untranslated regions (3′-UTRs) of their target mRNAs in a base-pairing manner, thereby causing mRNA degradation and/or translational suppression.…”
Section: Introductionmentioning
confidence: 99%
“…57 Another study found that miR-628 is regulated by SNHG16 and its target Neuropilin-1 (NRP1) can promote tumor metastasis. 58 SNHG16 was shown to promote cell invasion and migration in pancreatic cancer cells via mediating high mobility group box 1 (HMGB1) (a known oncogene in PC) expression through sponging miR-218-5p. 41 Wen et al found that knockdown of SNHG16 inhibits migration and invasion of TPC-1 cells via regulating miR-497.…”
Section: Activating Migration and Invasionmentioning
confidence: 99%
“…14 Another study found that miR-628 is regulated by SNHG16 and the expression of miR-628-3p is down in GC tissues and GC cell lines, and its target NRP1 can inhibit cell apoptosis. 58…”
Section: Inhibiting Apoptosismentioning
confidence: 99%